2016
DOI: 10.1120/jacmp.v17i4.6230
|View full text |Cite
|
Sign up to set email alerts
|

Validation of total skin electron irradiation (TSEI) technique dosimetry data by Monte Carlo simulation

Abstract: Total skin electron irradiation (TSEI) is a complex technique which requires many nonstandard measurements and dosimetric procedures. The purpose of this work was to validate measured dosimetry data by Monte Carlo (MC) simulations using EGSnrc‐based codes (BEAMnrc and DOSXYZnrc). Our MC simulations consisted of two major steps. In the first step, the incident electron beam parameters (energy spectrum, FWHM, mean angular spread) were adjusted to match the measured data (PDD and profile) at SSD=100 cm for an ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Compared with the papers of Schiapparelli et al [1] and Nevelesky et al [19] , the results can be confirmed in the proposed treatment methodology. We also concluded that the horizontal gantry angles should have an offset of ±19° to assure a homogenous coverage at the distance of 3.30 m required for our setup.…”
Section: Discussionsupporting
confidence: 73%
“…Compared with the papers of Schiapparelli et al [1] and Nevelesky et al [19] , the results can be confirmed in the proposed treatment methodology. We also concluded that the horizontal gantry angles should have an offset of ±19° to assure a homogenous coverage at the distance of 3.30 m required for our setup.…”
Section: Discussionsupporting
confidence: 73%
“…Details of our linac simulation have been described preciously . Briefly, the incident electron beam parameters (energy spectrum, FWHM, mean angular spread) were adjusted first to match the measured data (PDD and profile) at SSD = 100 cm for an open field.…”
Section: Methodsmentioning
confidence: 99%
“…and six dual fields (Stanford technique) were evaluated. Nevelesky et al [11] simulated a full TSEI treatment in an anthropomorphic phantom by the Monte Carlo method and validated the measured dosimetry data by the Monte Carlo (MC) simulations thanks to EGSnrc-based codes (BEAMnrc and DOSXYZnrc). The BEAMnrc code has high precision in the simulation of the material and electron radiation fields [12,13].…”
Section: Jinst 13 P05029mentioning
confidence: 99%
“…DOSXYZnrc [15] simulates the transport of photons and electrons in a Cartesian volume and scores the energy deposition in the designated voxels. The output of DOSXYZnrc calculations is a file that stores the calculated 3D dose distribution data and the corresponding dose uncertainties [11].…”
Section: Monte Carlo Simulationmentioning
confidence: 99%